Estimating the value of crop diversity conservation services provided by the Czech National Programme for Agrobiodiversity - Nicholas Tyack; Milan Scasny (Charles University in Prague, Institute of Economic Studies (IES), 2018)
We estimate the willingness-to-pay (WTP) for conserving crop varieties for ten years in the Czech Republic using a double-bounded dichotomous choice model to analyze data collected with an online contingent valuation survey administered to a main country-wide sample of 1037 respondents and a smaller sub-sample of 500 representative of the agricultural region of South Moravia. Mean WTP was found to be about 9 for both the Czech and S. Moravian sub-samples, corresponding to country-wide benefits of 68 million. These benefits increase by 5% for every ten varieties conserved, implying total welfare benefits of 80 million for a program conserving the maximum number of 35 additional crop varieties. The study reveals the previously unmeasured social benefits of crop conservation activities in the Czech Republic, and illustrates an empirical approach of potential value for policymakers responsible for determining funding levels for genetic resource conservation.
Keywords: Q18; Q51; Q57; 330; Crop diversity; plant genetic resources for food and agriculture (PGRFA); public goods; contingent valuation; double-bounded dichotomous choice